Preparation method and application of metal nitrogen and carbon loaded high-loading-capacity platinum catalyst

By using the first impregnation and then polyol reduction method in the fuel cell catalyst, the problem of easy agglomeration and falling off by high-load platinum-based catalysts is solved, and the uniform distribution and small size of platinum particles are achieved, and the stability and activity of the catalyst is improved, which is better than that of commercially available catalysts.

CN119864437APending Publication Date: 2025-04-22BEIJING UNIV OF TECH
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202510051354.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The existing high-load platinum-based catalysts are prone to agglomeration and fall off, resulting in low efficiency of cathode oxygen reduction reaction in fuel cells and degradation of catalyst stability and performance under high platinum load.

Method used

Using the method of impregnation first and then polyol reduction, a 40% loading of 3nmPt/MNC (M=Zn,Co,Ni) catalyst was designed and prepared. By adjusting the charge transfer between the support and the platinum particles, it enhanced its interaction, thereby achieving uniform distribution and small size of the platinum particles.

Benefits of technology

The uniform dispersion and small size of platinum particles are achieved, the stability and catalytic activity of the catalyst are improved, and it is better than the commercially available Pt/C catalysts, and has good industrial application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119864437A_ABST
    Figure CN119864437A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a metal nitrogen-carbon loaded high-load platinum catalyst, and belongs to the field of four-electron oxygen reduction. The method comprises the following steps: firstly, dispersing a synthesized metal carrier in ethylene glycol, carrying out uniform ultrasonic treatment, dropwise adding a chloroplatinic acid solution, continuously carrying out uniform ultrasonic dispersion, dropwise adding sodium hydroxide until the pH value is 11, and stirring for 2 hours; reacting the reaction liquid in an oil bath at 125 DEG C for 3 hours, cooling to room temperature, adding hydrochloric acid to settle the reaction liquid, washing with a large amount of water, and drying in vacuum to obtain the target catalyst. According to the synthesis method, relatively environment-friendly solvents such as methanol and ethylene glycol are used, so that the pollution to the environment is reduced, the used raw materials are relatively cheap, the energy consumption in the preparation process is relatively low, and the production cost of the catalyst is favorably reduced. The prepared catalyst shows excellent oxygen reduction performance and has a good industrial prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to electrochemical four-electron oxygen reduction, and in particular to a noble metal catalyst applied to a cathode oxygen reduction reaction in a fuel cell. Background Art

[0002] Proton exchange membrane fuel cells (PEMFCs) have been recognized as an important alternative energy source to fossil fuel combustion, enabling the transition to a carbon-neutral economy due to their ability to convert clean hydrogen into electricity with high efficiency and high energy density. In recent years, hydrogen fuel has received extensive attention for its application in heavy-duty vehicles due to its advantages such as high gravimetric energy density, high energy efficiency, fast refueling, zero emissions, and simple refueling infrastructure. PEMFCs will be a core technology for any envisioned "hydrogen economy" due to their ability to efficiently convert the chemical energy stored in hydrogen into usable electrical energy. However, the sluggish kinetics of the cathode oxygen reduction reaction (ORR) have significantly hampered their development. Various strategies have been adopted to improve the efficiency of cathode catalysis while reducing the use of platinum. These include PtM alloying (M: Fe, Co, Ni, Cu), and further control of PtM alloys with core-shell structures, optimized morphology / crystal planes, and ordered intermetallic structures. While these catalysts have shown remarkable performance at the rotating disk electrode (RDE) level, they often fail to provide satisfactory performance in membrane electrode assemblies (MEAs) at low Pt loadings. The main reasons for this problem are low O2 transport efficiency and increased voltage losses due to the high overpotential required to drive the reaction. A straightforward strategy to address this problem is to reduce the thickness of the catalytic layer (CL) of the MEA, which means that catalysts with higher Pt loading (weight percentage) are required.

[0003] However, high metal loadings can lead to significant aggregation and heterogeneity of nanoparticles, which can adversely affect the stability and performance of the catalyst. Existing commercial carbon supports often exacerbate this problem, typically lacking the optimal pore structure required to effectively anchor Pt particles. High Pt loadings can result in insufficient interactions with the carbon supports, and Pt nanoparticles on these commercial carbon materials can migrate, aggregate, or separate under dynamic fuel cell operating conditions, leading to severe ECSA loss and significant performance degradation. Therefore, exploring suitable carbon supports that can effectively accommodate high Pt loadings while maintaining stability and performance is critical to advancing PEMFC technology and improving ORR efficiency. In recent years, metal nitrogen carbon (MNC) materials have attracted extensive attention as effective supports for Pt due to their favorable properties, including diverse nanostructures, multi-level pore distributions, and abundant active sites. More importantly, utilizing MNCs rich in M-Nx active sites as supports is a novel and effective strategy and capability to enhance the interaction between the support and Pt particles by regulating the charge transfer between the support and Pt-based alloys. Summary of the invention

[0004] The purpose of the present invention is to solve the problems of easy agglomeration and shedding of existing high-load platinum-based catalysts, develop a Pt / MNC (M = Zn, Co, Ni) catalyst with uniformly dispersed platinum particles and small size, and provide a preparation method of the catalyst. The method adopts a method of first impregnation and then polyol reduction, and is designed to obtain a 40wt% loaded Pt / MNC (M = Zn, Co, Ni) catalyst with a high active site density of sub-3nm.

[0005] The technical solution adopted by the present invention is:

[0006] A method for preparing a metal nitrogen-carbon loaded high-load platinum catalyst comprises the following steps:

[0007] Step 1. Dissolve dimethylimidazole in methanol and stir evenly, which is recorded as solution A; dissolve cobalt nitrate and zinc nitrate in methanol and stir evenly, which is recorded as solution B; the molar ratio of dimethylimidazole to cobalt nitrate hexahydrate and zinc nitrate used is 40:1:5, the concentration of dimethylimidazole ion in solution A is 0.5mmol / ml, the concentration of cobalt nitrate hexahydrate ion in solution B is 0.0125mmol / ml, and the concentration of zinc nitrate hexahydrate ion is 0.06mmol / ml;

[0008] Step 2. Pour solution B into solution A and stir at room temperature;

[0009] Step 3. Filter the solution obtained in step 2 and wash with methanol, and dry the obtained solid in a vacuum oven at 60° overnight.

[0010] Step 4. Grind the powder in step 3 evenly, put it in a tube furnace and calcine it at 1000°C in an argon atmosphere for 3 hours, with a heating rate of 2° / min, cool it to room temperature and take it out to obtain a black powder; take the black powder and dissolve it in sulfuric acid, the molar ratio of the black powder to sulfuric acid is 3:1; react in a water bath at 80°C for 36 hours, wait for it to cool to room temperature, filter it, and wash it with distilled water, and dry the solid obtained by filtration in a vacuum oven at 60° overnight; grind it evenly in a mortar to obtain a CoNC carrier;

[0011] Step 5. Take the MNC carrier, dissolve it in ethylene glycol, and sonicate for 1 h;

[0012] Step 6. Add chloroplatinic acid precursor solution dropwise to the solution in step 5, the molar ratio of the carrier to chloroplatinic acid is 6:7, the concentration of platinum ions in the chloroplatinic acid precursor solution is 0.00032 mmol / ml, and continue ultrasonication;

[0013] Step 7. Add the prepared 3M sodium hydroxide solution to the solution in step 6 to adjust the pH to 11, and stir the solution on a magnetic stirrer for 2 hours;

[0014] Step 8. Place the solution in step 7 in an oil bath at 125°C for 3 hours, and add circulating cooling water for protection; after the reaction solution is cooled to room temperature, hydrochloric acid is added to precipitate the reaction solution, and black solid will precipitate after the addition of hydrochloric acid; filter and wash with water to remove ethylene glycol and chloride ions in the sample, place in a vacuum oven at 60° and dry overnight to obtain a Pt / MNC catalyst.

[0015] Furthermore, in step 2, the stirring time at room temperature is 24 hours.

[0016] Further, in step 4, the concentration of sulfuric acid used is 2M.

[0017] Further, in step 6, the ultrasonic time is 1 h.

[0018] Furthermore, in step 8, the concentration of the added hydrochloric acid solution is 0.1 M, and the volume ratio of the hydrochloric acid solution to the reaction solution is 4:1.

[0019] The prepared catalyst is used as a membrane electrode cathode catalyst in the oxygen reduction reaction of a fuel cell membrane electrode.

[0020] The present invention has the following advantages:

[0021] 1. The present invention uses ethylene glycol reduction followed by impregnation during the synthesis process, which can achieve uniform distribution of high-load platinum. The pH value is adjusted by NaOH to control the platinum particle size to about 3 nm, ensuring that the catalyst has a stronger catalytic ability in the reaction, thereby improving the energy conversion efficiency of the fuel cell.

[0022] 2. This method uses relatively environmentally friendly solvents such as methanol and ethylene glycol, which reduces pollution to the environment and complies with the principles of green chemistry.

[0023] 3. The raw materials used in this method are relatively cheap, and the energy consumption in the preparation process is low, which helps to reduce the production cost of the catalyst.

[0024] 4. The Pt / MNC catalyst synthesized by this method exhibits enhanced catalytic activity and stability, and exhibits excellent mass activity (MA) and specific activity (SA) at 0.9 V, which is better than the commercially available Pt / C catalyst. It has good prospects for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The preparation flow chart of Pt / MNC (M=Zn,Co,Ni) catalyst

[0026] Figure 2 XRD pattern of Pt / MNC (M=Zn,Co,Ni) catalyst

[0027] Figure 3 TEM image of Pt / CoNC catalyst

[0028] Figure 4 Electrochemical performance diagram of Pt / MNC (M=Zn,Co,Ni) DETAILED DESCRIPTION

[0029] The present invention is further described in detail below with reference to the accompanying drawings and embodiments.

[0030] Example 1

[0031] Dissolve 13.14g of dimethylimidazole in 160ml of methanol and stir evenly, record as solution A. Dissolve 5.95g of zinc nitrate hexahydrate and 1.164g of cobalt nitrate hexahydrate in 160ml of methanol and stir evenly, record as solution B. Pour solution B into solution A and stir at room temperature for 24h. Filter the stirred solution and wash with 100ml of methanol. Dry the obtained solid in a vacuum oven at 60° for one night. Grind the powder evenly and place it in a tube furnace for calcination at 1000° in an argon atmosphere for 3h, with a heating rate of 2° / min. Cool to room temperature and take out to obtain a black powder. Take 300mg of black powder, dissolve it in 150ml of 2M sulfuric acid solution, react in a water bath at 80° for 36h, wait for it to cool to room temperature and filter it, wash it with 1000ml of distilled water, and dry the solid obtained by filtration in a vacuum oven at 60° for one night. Grind evenly in a mortar to obtain an NC carrier. Take 50 mg of NC carrier, dissolve it in 50 ml of ethylene glycol, ultrasonicate for 1 hour, add 5 ml of chloroplatinic acid precursor solution (20 g / L) dropwise to the solution, continue ultrasonicate for 1 hour, add 3M sodium hydroxide solution prepared in advance to the solution to adjust the pH to 11, stir it on a magnetic stirrer for 2 hours, place it in an oil bath at 125° for 3 hours, and add circulating cooling water for protection. After the reaction solution is cooled to room temperature, add 200 ml of 0.1M hydrochloric acid solution to precipitate the reaction solution. After adding hydrochloric acid, black solid will precipitate. Filter and wash with a large amount of water to remove ethylene glycol and chloride ions on the surface of the sample, place it in a vacuum oven at 60° to dry overnight to obtain a Pt / CoNC catalyst. The preparation process is as follows Figure 1 The catalyst was subjected to XRD phase analysis, as shown Figure 2 As shown, XRD showed peaks of platinum, indicating successful loading of platinum. Figure 3 As shown in Figure 1, platinum nanoparticles are evenly distributed on the cobalt nitrogen carbon support. Figure 4 The onset potential and half-wave potential of the catalyst are shown to be 1.02 V and 0.88 V, respectively.

[0032] Example 2

[0033] Dissolve 13.14g of dimethylimidazole in 160ml of methanol and stir evenly, record as solution A. Dissolve 5.95g of zinc nitrate hexahydrate in 160ml of methanol and stir evenly, record as solution B. Pour solution B into solution A and stir at room temperature for 24h. Filter the stirred solution and wash with 100ml of methanol. Dry the obtained solid in a vacuum oven at 60° for one night. Grind the powder evenly, put it in a tube furnace and calcine it under 1000° argon atmosphere for 3h, with a heating rate of 2° / min, cool to room temperature and take it out to obtain a black powder. Take 300mg of black powder, dissolve it in 150ml of 2M sulfuric acid solution, react in a water bath at 80° for 36h, wait until it cools to room temperature and filter it, wash it with 1000ml of distilled water, and dry the solid obtained by filtration in a vacuum oven at 60° for one night. Grind evenly in a mortar to obtain an NC carrier. Take 50 mg of NC carrier, dissolve it in 50 ml of ethylene glycol, ultrasonicate for 1 hour, add 5 ml of chloroplatinic acid precursor solution (20 g / L) dropwise into the solution, continue ultrasonicate for 1 hour, add the prepared 3M sodium hydroxide solution into the solution to adjust the pH to 11, stir it on a magnetic stirrer for 2 hours, place it in an oil bath at 125° for 3 hours, and add circulating cooling water for protection. After the reaction solution is cooled to room temperature, add 200 ml of 0.1M hydrochloric acid solution to precipitate the reaction solution. After adding hydrochloric acid, black solid will precipitate. Filter and wash with a large amount of water to remove the ethylene glycol and chloride ions on the surface of the sample, place it in a vacuum oven at 60° to dry overnight to obtain a Pt / NC catalyst. The preparation process is as follows Figure 1 The catalyst was subjected to XRD phase analysis, as shown Figure 2 As shown, XRD showed peaks of platinum, indicating successful loading of platinum. Figure 4 The onset potential and half-wave potential of the catalyst are shown to be 0.96 V and 0.85 V, respectively.

[0034] Example 3

[0035] Dissolve 13.14g of dimethylimidazole in 160ml of methanol and stir evenly, record as solution A. Dissolve 5.95g of zinc nitrate hexahydrate and 1.5g of nickel nitrate hexahydrate in 160ml of methanol and stir evenly, record as solution B. Pour solution B into solution A and stir at room temperature for 24h. Filter the stirred solution and wash with 100ml of methanol. Dry the obtained solid in a vacuum oven at 60° for one night. Grind the powder evenly, put it in a tube furnace and calcine it under 1000° argon atmosphere for 3h, with a heating rate of 2° / min, cool to room temperature and take it out to obtain a black powder. Take 300mg of black powder, dissolve it in 150ml of 2M sulfuric acid solution, react in a water bath at 80° for 36h, wait until it cools to room temperature and filter it, wash it with 1000ml of distilled water, and dry the solid obtained by filtration in a vacuum oven at 60° for one night. Grind evenly in a mortar to obtain an NC carrier. Take 50 mg of NC carrier, dissolve it in 50 ml of ethylene glycol, ultrasonicate for 1 hour, add 5 ml of chloroplatinic acid precursor solution (20 g / L) dropwise to the solution, continue ultrasonicate for 1 hour, add the 3M sodium hydroxide solution prepared in advance to the solution to adjust the pH to 11, stir it on a magnetic stirrer for 2 hours, place it in an oil bath at 125° for 3 hours, and add circulating cooling water for protection. After the reaction solution is cooled to room temperature, add 200 ml of 0.1M hydrochloric acid solution to precipitate the reaction solution. After adding hydrochloric acid, black solids will precipitate. Filter and wash with a large amount of water to remove ethylene glycol and chloride ions on the surface of the sample, place it in a vacuum oven at 60° to dry overnight to obtain a Pt / NiNC catalyst. The preparation process is as follows Figure 1 The catalyst was subjected to XRD phase analysis, as shown Figure 2 As shown, XRD showed peaks of platinum, indicating successful loading of platinum. Figure 4 The onset potential and half-wave potential of the catalyst are shown to be 1.01 V and 0.87 V, respectively.

[0036] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a metal nitrogen-carbon loaded high-load platinum catalyst, characterized in that: The following steps are involved: Step 1. Dissolve dimethylimidazole in methanol and stir evenly, which is recorded as solution A; dissolve cobalt nitrate and zinc nitrate in methanol and stir evenly, which is recorded as solution B; the molar ratio of dimethylimidazole to cobalt nitrate hexahydrate and zinc nitrate used is 40:1:5, the concentration of dimethylimidazole ion in solution A is 0.5mmol / ml, the concentration of cobalt nitrate hexahydrate ion in solution B is 0.0125mmol / ml, and the concentration of zinc nitrate hexahydrate ion is 0.06mmol / ml; Step 2. Pour solution B into solution A and stir at room temperature; Step 3. Filter the solution obtained in step 2 and wash with methanol, and dry the obtained solid in a vacuum oven at 60° overnight. Step 4. Grind the powder in step 3 evenly, put it in a tube furnace and calcine it at 1000°C in an argon atmosphere for 3 hours, with a heating rate of 2° / min, cool it to room temperature and take it out to obtain a black powder; take the black powder and dissolve it in sulfuric acid, the molar ratio of the black powder to sulfuric acid is 3:1; react in a water bath at 80°C for 36 hours, wait for it to cool to room temperature, filter it, and wash it with distilled water, and dry the solid obtained by filtration in a vacuum oven at 60° overnight; grind it evenly in a mortar to obtain a CoNC carrier; Step 5. Take the MNC carrier, dissolve it in ethylene glycol, and sonicate for 1 h; Step 6. Add chloroplatinic acid precursor solution dropwise to the solution in step 5, the molar ratio of the carrier to chloroplatinic acid is 6:7, the concentration of platinum ions in the chloroplatinic acid precursor solution is 0.00032 mmol / ml, and continue ultrasonication; Step 7. Add the prepared 3M sodium hydroxide solution to the solution in step 6 to adjust the pH to 11, and stir the solution on a magnetic stirrer for 2 hours; Step 8. Place the solution in step 7 in an oil bath at 125°C for 3 hours, and add circulating cooling water for protection; after the reaction solution is cooled to room temperature, hydrochloric acid is added to precipitate the reaction solution, and black solid will precipitate after the addition of hydrochloric acid; filter and wash with water to remove ethylene glycol and chloride ions in the sample, place in a vacuum oven at 60° and dry overnight to obtain a Pt / MNC catalyst.

2. The method for preparing a metal nitrogen-carbon-loaded high-load platinum catalyst according to claim 1, characterized in that: In step 2, the stirring time at room temperature is 24 h.

3. The method for preparing a metal nitrogen-carbon-loaded high-load platinum catalyst according to claim 1, characterized in that: In step 4, the concentration of sulfuric acid used is 2M.

4. The method for preparing a metal nitrogen-carbon-loaded high-load platinum catalyst according to claim 1, characterized in that: In step 6, the ultrasonication time is 1 h.

5. The method for preparing a metal nitrogen-carbon-loaded high-load platinum catalyst according to claim 1, characterized in that: In step 8, the concentration of the added hydrochloric acid solution is 0.1 M, and the volume ratio of the hydrochloric acid solution to the reaction solution is 4:

1.

6. A catalyst prepared by the method of claim 1, characterized in that: Used as membrane electrode cathode catalyst in the oxygen reduction reaction of fuel cell membrane electrode.

Citation Information

Cited By

  • Carbon-supported platinum-cobalt-copper multifunctional alloy catalyst as well as preparation method and application thereof

    CN120280503A

  • Preparation method and preparation device of nano platinum powder

    CN120438638A

  • Chiral molecule Pt-based alloy catalyst with high oxygen reducibility as well as preparation method and application of chiral molecule Pt-based alloy catalyst

    CN120749174A